PENGARUH PEER SOCIAL SUPPORT, INTERPERSONAL COMMUNICATION DAN EMOTIONAL INTELLIGENCE TERHADAP PENYESUAIAN SOSIAL MAHASISWA RANTAU DI SALAH SATU KAMPUS DI JAKARTA SELATAN - Erni Rizki Wulandini; Arif Murti Rozamuri (Jurnal GeoEkonomi, 2024)
The unevenness of educational development in Indonesia causes inequality in the quality of education in rural and urban areas. In Indonesia, it is recorded that 13.21% of urban people continue their education to tertiary institutions, while in rural areas it is only 3.84%. This causes many high school and vocational school graduate students from rural areas to choose to migrate with the aim of getting a better quality education. One of the campuses in South Jakarta is a campus that is a destination for overseas students because the number of students on that campus is dominated by students from outside JABODETABEK. The aim of this research is to find out how overseas students go through a period of social adaptation or adjustment in terms of the aspects of peer social support, interpersonal communication and emotional intelligence. This type of research is quantitative research with data collection using questionnaires via Likert scale measurements. In this research, there were 277 samples from the total number of overseas students in all 2022 class study programs on the campus, which were taken using a simple random sampling method. Quantitative analysis is carried out through the application of multiple linear analysis. The results of this research show that the three variables simultaneously have a significant effect on the social adjustment of overseas students by 64.5%. Keywords: Peer Social Support, Interpersonal Communication, Emotional Intelligence, Social Adjustment.